Membrane behavior in RC slabs subjected to simulated reinforcement corrosion. (15th September 2016) - Botte, Wouter; Caspeele, Robby; Taerwe, Luc
Highlights: The influence of corrosion on membrane behavior in RC slabs was investigated. The load-bearing capacity is significantly reduced even at small corrosion levels. In case of compressive membrane action, concrete deterioration should be considered. The determining factor for failure is the ultimate strain of the reinforcement. Abstract: Deterioration due to corrosion has been a growing concern in the last decades since it compromises the serviceability of structures and results in a decrease of the structural safety. Apart from deterioration, also the awareness of the importance of structural robustness has increased due to several failures with progressive collapse. The activation of membrane action in reinforced concrete slabs can significantly increase the structural robustness by providing an alternate load path. A validated numerical model for the tensile membrane behavior of reinforced concrete slabs is used to investigate the influence of (simulated) corrosion effects on this membrane behavior. A two-step analysis is adopted: first a cross-section analysis is performed, followed by an analysis of the structural member. It was observed that even for small corrosion levels, there was a significant influence on the ultimate bearing capacity of the slab. Finally, also the influence of different corrosion locations was investigated.